Building Image Through Food Choice: The Effects of Unfamiliar Companion, Impression Management, and Emotional Eating on Food Portion - Aqilah Az Zahra; Anna Undarwati (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2024)
The global rise in the obesity epidemic is largely driven by the consumption of foods that contribute to significant health risks. This research study focuses on the social and personal factors that influence food portions, in addition to environmental factors. The study is designed to investigate the effect of unfamiliar companion, impression management, and emotional eating on food portions in Indonesia. The study employed a quasi-experimental research design in a laboratory setting, using a fake food buffet by recruiting 245 undergraduate students. The results indicated that unfamiliar companion, impression management, and emotional eating had a significant main effect and interaction effect on individuals' food portions (p < 0.05). This was demonstrated by the difference in food portion between people eating alone and in the presence of an unfamiliar companion. It might explain that individuals are aware of maintaining a positive image during meals by choosing food portions that are perceived to reflect positive perceptions when dining with a person who lacks familiarity or personal connection. The research findings can be utilised as a reference for fundamental understanding of mitigation strategies for reducing food portions among adults.